2017
DOI: 10.1111/tid.12754
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and long‐term outcomes of parvovirus B19 infection in kidney transplant patients

Abstract: The identification of factors related to positive parvovirus B19 PCR results may promote the early detection of parvovirus B19 infection. Further studies are needed to elucidate the characteristics of parvovirus B19 infection in kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Few studies have been carried out worldwide on the detection of B19V DNA in patients under dialysis; most surveys have been focused on the prevalence of B19V in kidney transplant recipients (Rosado-Canto et al, 2019;Hai An et al, 2019;Baek et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been carried out worldwide on the detection of B19V DNA in patients under dialysis; most surveys have been focused on the prevalence of B19V in kidney transplant recipients (Rosado-Canto et al, 2019;Hai An et al, 2019;Baek et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The epidemiology of parvovirus B19 and parvovirus B19-related anemia after KTx remains unclear. [ 5 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Baek et al [13] showed that nearly 90% of positive cases were reported within the first year after kidney transplantation. The major risk factor for parvovirus B19 infection is immunosuppression, which is shown due to resolution of anemia when immunosuppression is lowered [14].…”
Section: Discussionmentioning
confidence: 99%